The applicability of King-Devick test in early detection of cognitive impairments due to induced hypoxia in military pilots - S Ehteshami; A Nezami Asl; A Khademi; R Eslami; S Riahi; HR Mohsenzadeh (فصلنامه ابن سینا)
Background: Hypoxia is one of the major threats to human health in high altitude. Considering the importance of hypoxia experience by military pilots and educating them how to deal with this condition, this study was designed to assess the applicability of King-Devick (K-D) test in early recognition of cognitive impairments due to induced hypoxia. Materials and methods: Totally, 60 military pilots who were candidate to experience hypoxia in hypobaric chamber were randomly enrolled the study. Study process included the following steps: training, filling the questionnaire, K-D test in normoxic condition, denitrogenation, preparation for hypoxia, Eustachian tube performance test, simulating 25,000 ft altitude, K-D test in hypoxic condition, reusing oxygen mask. Results: The mean age of candidates was 31.78±7.74 years. About 46.7% of them had normal weight and 53.3% were overweight and 31.7% were smokers. The average flight time was 1168.35±1345.21 hours. The average K-D time in normoxic condition was 45.54±5.43 seconds and 71.7% of pilots had no mistake in reading numbers. The mean K-D time in hypoxic condition was 52.98±5.86 and 98.3% of pilots made 1 to 11 mistakes. Results show that smokers significantly had longer K-D time than non-smokers. There was no other significant difference between groups in terms of average K-D time and number of mistakes. Conclusion: It seems that this study was the first one using K-D test in early recognition of cognitive impairments due to induced hypoxia in military pilots. It revealed that smoking significantly increases K-D time. Other factors like age, weight, and flight time did not show significant impact on K-D time and number of errors.